Monitoramento remoto e seguro do campo magnético em linhas de transmissão de alta tensão - Montero, Ciro José Egoavil (2017)
Magnetic and electric field levels monitoring in overhead transmission lines (TL) of power plants and substations (SEs) has been established by Brazilian Resolution 616/2014. It was observed in procedures to carry out SEs magnetic and electric field levels measurements, that it is necessary to have a methodology that allows levels continuous monitoring generated by power equipment. This monitoring procedure must be carried out in such a way that levels recording will be accomplished without occupational public exposure that will perform electromagnetic irradiation studies in the courtyard where equipment and machines that generate electric power system are located. The methodology for measuring magnetic field levels of overhead TLs will be carried out through a sensors network, whose values will be transmitted to a supervisory scheme. Simultaneously, an antenna designed to read the generated field, will collect the levels following a movement that must cover TL monitored area. The antenna was positioned at a distance specified by work safety area. Recorded data were acquired, processed, compared and analyzed in such a way that areas with high irradiation levels, so forth areas with acceptable levels and safe areas could be determined. This thesis aims to acquire remotely magnetic flux density levels produced around the TL, reducing the implementing monitoring costs and providing information to occupational public of existing irradiation levels by continuous recording of electromagnetic levels in TL area near generating units and SE installations where magnetic field highest levels are found.